9 elements of family business success a proven formula for improving leadership & relationships in family businesses - Fishman, Allen E. (McGraw-Hill professional, 2009)
This book features a time-tested process for taking a family business from a personal dream to a profitable growth enterprise. Allen Fishman, Founder and CEO of The Alternative Board (TAB), his own successful family-run business, presents a unique nine-step strategy for owning and running a family business. "9 Elements of Family Business Success" offers valuable insights that help you run a family business, and it addresses the specific problems that face family-owned enterprises. Fishman shows you how to create and share personal value statements, bring in and develop family members, resolve conflicts within the family, manage non-family employees, and much more.